2023
DOI: 10.3390/app13021137
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Versus Perceived Comfort and Health in Office Buildings at Western Macedonia Area, Greece during the Pandemic Period

Abstract: This study investigated the indoor environment quality (IEQ) of eight office buildings of interest due to: (a) their location at the region of Western Macedonia, Greece, which is an area characterized by aggravated air quality and is currently in a transition phase because of changes in the energy production strategy to reduce the use of lignite as an energy fuel; and (b) the survey’s timing, characterized by new working conditions implemented during the COVID-19 pandemic period. In-site measurements were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…According to Zamani, Jalaludin and Shaharom, 140 furniture, equipment and other objects release VOCs, and when their concentrations exceed 0.124 ppm, individuals are approximately 14.1 times more likely to develop SBS. 141 Sakellaris et al 142 associated cancer risk with formaldehyde concentration. Miller et al 143 found that 70% of health problems were related to exposure to mould odours.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zamani, Jalaludin and Shaharom, 140 furniture, equipment and other objects release VOCs, and when their concentrations exceed 0.124 ppm, individuals are approximately 14.1 times more likely to develop SBS. 141 Sakellaris et al 142 associated cancer risk with formaldehyde concentration. Miller et al 143 found that 70% of health problems were related to exposure to mould odours.…”
Section: Discussionmentioning
confidence: 99%